Pakistan : Selected Issues Paper. (IMF Staff Country Reports; Country Report ;, 2016)
This Selected Issues paper reviews Pakistan's tax regime, evaluates the level and composition of tax revenues, and estimates tax buoyancy and efficiency. Despite recent progress under the program, Pakistan's tax revenue remains very low relative to comparator developing countries and the tax effort expected for the country's level of development. This reflects narrow tax bases, overgenerous tax concessions and exemptions, weak and fragmented revenue administrations, and structural features of the economy. The findings suggest that unlocking tax revenue potential requires broadening tax bases, strengthening revenue administration and taxpayer compliance, eliminating distortionary tax expenditures, and rationalizing tax policy for greater efficiency and equity through a comprehensive and front-loaded reform agenda.